Модель резонансного транзисторного інвертора напруги з низькочастотною імпульсною модуляцією - Юрченко, О.М.; Гуцалюк, В.Я.; Герасименко, П.Ю.; Слєсаревський, І.О. (Технічна електродинаміка, 2011)
In the article it is considered the bridge-type voltage inverter circuit to the output of which it is connected the inductor with heated body and balancing capacitor through the matching transformer. The inverter load substitution circuit can be represented as series-resonant circuit which consists of the inductance L, capacity C and active resistance R.